Haloid acid induced carbon nitride semiconductors for enhanced photocatalytic H2 evolution and reduction of CO2 under visible light. (November 2018) - Wan, Shipeng; Ou, Man; Zhong, Qin; Cai, Wei
Abstract: Hexagonal tubular carbon nitride (CN) was successfully fabricated from hexagonal rod-like supramolecular precursor. The supramolecular precursor was synthesized by hydrogen bonded self-assembly of melamine and cyanuric acid, in which cyanuric acid was from in-situ hydrolysis of melamine under haloid acid-assisted hydrothermal environment. The obtained hexagonal tubular CNs not only possess hierarchical micro-nanostructure, increased specific surface area, together with an enlarged band gap energy of 2.85 ± 0.05 eV, but also show better light absorption capacity in visible to near-infrared region and improved separation rate of photogenerated carriers. Therefore, they exhibit enhanced photocatalytic reduction performance on water splitting to H2, the largest hydrogen evolution rate can reach 2948.5 μmol g −1  h −1, which is better than most reported CNs. Simultaneously, they also have excellent photocatalytic reduction ability on the conversion of CO2 to H2, CO and CH4, exhibiting higher averaged electron consumption than previously reported semiconductor photocatalysts. Finally, the photocatalytic reduction mechanism over the synthetic tubular CN is proposed and discussed. Graphical abstract: Image 1